T-wave depletion and bradycardia possibly secondary to acute pancreatitis: Review of the literature - Cansel TÜRKAY; Timuçin AYDOĞAN; Aydın KARANFİL and Mehtap ERKMEN UYAR and Yusuf SELÇOKİ and Mehmet KANBAY (Turkish Journal of Gastroenterology, 2019)
-